For Whom the Clock Ticks: Clinical Chronobiology for Infectious Diseases - Diallo, Aïssatou Bailo; Coiffard, Benjamin; Leone, Marc; Mezouar, Soraya; Mege, Jean-Louis (Frontiers in Immunology, 2020)
The host defense against pathogens varies among individuals. Among the factors influencing host response, those associated with circadian disruptions are emerging. These latter depend on molecular clocks, which control the two partners of host defense: microbes and immune system. There is some evidence that infections are closely related to circadian rhythms in terms of susceptibility, clinical presentation and severity. In this review, we overview what is known about circadian rhythms in infectious diseases and update the knowledge about circadian rhythms in immune system, pathogens and vectors. This heuristic approach opens a new fascinating field of time-based personalized treatment of infected patients.